An analysis of Clinical, Ultrasonological and Cytopathological findings of thyroid swellings at a teaching hospital in eastern Nepal - Thakur, S.K.; Thakur, R.; Nepal, N.; Khanal, T.; Adhikari, A.; Yadav, R.K.; Ghimire, N. (Journal of Diabetes and Endocrinology Association of Nepal, 2022)
Background: Thyroid swelling can be benign or malignant. It is evaluated by clinical examination, Ultrasonography (USG) and Fine Needle Aspiration Cytology (FNAC). This study was conducted with the aim of comparing discrepancy of diagnosis by USG, considering FNAC as gold standard. Methods: A prospective observational study of thyroid swellings with convenient sampling was carried out over a year (20 October 2020 to 19 October 2021) at Outpatient department of Nobel Medical College, Biratnagar, eastern region of Nepal. Clinical, ultrasonological and cytological parameters were recorded. Sensitivity, Specificity, Positive predictive value (PPV) and negative predictive value (NPV) were calculated. Results: Out of 120 study population, with a mean age of 45.37 years, there was female preponderance, 110(91.66%). The commonest age group was 30-40 years, 28(23.33%). On Ultrasonography, non neoplastic lesions diagnosed were in 104 (86.7%) cases, as compared to FNAC, 113(94.2%). While, malignancy was diagnosed in 16 (13.7%) cases, by USG, only 7(5.8%) cases were malignant on FNAC. The Sensitivity of USG for malignancy detection was 100%, Specificity was 92 %, Positive predictive value (PPV) was 43.75 % and Negative Predictive value (NPV) was 100% as compared to FNAC. Accuracy was 92.5%. Conclusions: Ultrasonography has an excellent diagnostic sensitivity, specificity and accuracy compared to that of FNAC.